National Coaching Certification Program
Sport plays an important role in the lives of many Canadians. Quality coaching is key to a positive sport experience for participants. Sport, government, and business leaders recommend that all coaches become trained and certified in the National Coaching Certification Program (NCCP) to ensure that the sport experience of every participant is a good one.